2023
DOI: 10.1136/bmj-2022-073343
|View full text |Cite
|
Sign up to set email alerts
|

Integrating perinatal mental healthcare into maternal and perinatal services in low and middle income countries

Abstract: Gergana Manolova and colleagues argue for a comprehensive approach to the challenge of treating perinatal mental health conditions in maternal, neonatal, and child health services

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, our findings show that anxiety disorders may add significantly to the burden of perinatal mental health disorders in LMICs, and this burden needs urgent attention. The integration of perinatal mental health care into universal maternal and child health services is crucial . Screening and treatment options are needed that are culturally appropriate and that cover the breadth of mental health disorders, including anxiety and related disorders, and not simply depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings show that anxiety disorders may add significantly to the burden of perinatal mental health disorders in LMICs, and this burden needs urgent attention. The integration of perinatal mental health care into universal maternal and child health services is crucial . Screening and treatment options are needed that are culturally appropriate and that cover the breadth of mental health disorders, including anxiety and related disorders, and not simply depression.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Manolova and colleagues (2023) talk about the concept of “voltage drop”, where a program with high efficacy may not achieve high effectiveness in the real world ( 24 ). Studies evaluating (cost)effectiveness and feasibility of existing interventions and programmes are both important for care development and often lacking.…”
Section: Future Directionsmentioning
confidence: 99%
“…Ransing et al (2020) reported that a wide knowledge gap about perinatal depression exists among perinatal women, nurses, and medical practitioners. There are not adequate healthcare providers trained in maternal, newborn, and child mental health, which goes a long way to affect services' ability to identify mental health conditions, provide psychosocial interventions for their prevention and management, and make referrals appropriately (Manolova et al, 2023).…”
Section: Introductionmentioning
confidence: 99%